The Relationship between Mother Tongue Domination and Language Attitudes of DPKU IPB Students Class of 62 - Risa Prayudhi; Mukhlas Ansori; Renny Soelistiyowati; Dewi Indriani (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study aims to analyze the relationship between mother tongue dominance and the language attitudes of IPB students in the 62nd batch. The background of this study is based on the phenomenon of language shift and maintenance in a multicultural university environment where students are faced with the demands of using regional languages, national languages, and global languages. The research method used was quantitative with a cross-sectional survey approach. Data collection instruments included a mother tongue dominance questionnaire adapted from the Bilingual Language Profile (BLP) and a language attitude scale based on cognitive, affective, and conative dimensions adapted from Baker (1992). The data were analyzed using SPSS 27 through validity and reliability tests, descriptive statistical analysis, normality tests, and Pearson's correlation test. The results showed a positive and significant relationship between mother tongue dominance and students' language attitudes, with a correlation coefficient of 0.213 and a significance of 0.009 (< 0.05). Although the strength was relatively weak, this finding confirmed that the more dominant the use of the mother tongue, the more positive the students' attitudes toward that language. IPB students of Class 62 showed positive attitudes towards their mother tongue, but remained adaptive to the use of national and international languages in the academic environment. This finding emphasizes the importance of preserving the mother tongue among students as part of preserving cultural identity and strengthening multilingual awareness. This study also recommends that campuses develop programs based on regional culture and language as a form of support for linguistic diversity in higher education. Keywords: Mother Tongue Dominance, Language Attitude, IPB Students, Bilingualism, Multilingualism.